Temporal dimensions of vulnerability to crime in economic sectors - Klima, Noel (2011)
This paper presents the results of research into vulnerability to crime in two economic sectors in Belgium. Vulnerability to crime is an integration of diverse temporal factors. We address pre-crime and post-crime aspects of vulnerability, arising before and after the criminal event in an economic context. Based on interviews with professionals, security staff, law enforcement agents and with criminals in the transport sector and the hotel and catering industry, a study of police files, and inspired by ecologists’ work on resilience, we explore vulnerability to crime as a multifaceted factor undermining the sustainability of businesses